Copper‐Catalyzed Reaction Cascade of Thiophenol Hydroxylation and S‐Arylation through Disulfide‐Directed C−H Activation. Issue 16 (9th March 2016) - Wang, Dawei; Yu, Xin; Yao, Wei; Hu, Wenkang; Ge, Chenyang; Shi, Xiaodong
Abstract: Copper‐catalyzed thiophenol C−H activation is described. Through an initial attempt to conduct C‐arylation with arylboronic acid, a rather surprising sequential C−H activation and S‐arylation was discovered. Mechanistic investigation revealed the disulfide intermediate as the key component in directing C−H oxidation. The overall reaction proceeded under mild conditions with molecular oxygen as the oxidant. Discovery of disulfide as the directing group provides a potential new direction for catalytic C−H functionalization under mild conditions. Abstract : Copper‐catalyzed thiophenol C−H activation is described. In an initial attempt to conduct C‐arylation with arylboronic acid, a rather surprising sequential C−H activation and S‐arylation was discovered. Mechanistic investigation revealed the disulfide intermediate as the key component in directing C−H oxidation. The overall reaction proceeds under mild conditions with molecular oxygen as an oxidant. Discovery of disulfide as the directing group provides a potentially new direction for catalytic C−H functionalization under mild conditions.